(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
Recent investigations on gender have shown that they do not constitute a multi-centered arena of knowledge production. But, that there is a clear division between center and peripherias, strongly influenced by the United States as a hegemonic centre in theoretical production (Wöhrer, 2016). This paper follows Walter Benjamin ́s suggestion to write a countercurrent History, which means, firstly, to appropriate critical elements to denounce various faces of epistemic injustice (Fricker, 2007). This concept will help us to illustrate how in Latin America, materialist francophone feminism interweaved together many other silenced contributions. To reconstruct those streams is political as it restitutes a plurality of voices and exhibits how epistemic or cognitive extractivism favors feminism not only to revise theories but also practices. This is how Colette Guillaumin’s critical Concepts help to revise and give voice to many “mude concepts” present in the Gender Studies Western Canon, especially when analyzing racism.